Generation and degeneration : tropes of reproduction in literature and history from antiquity through early modern Europe - Finucci, Valeria; Brownlee, Kevin (E-Duke books scholarly collection., 2001)
This collection explores the construction of genealogies both in the biological sense of procreation and in the metaphorical sense of heritage and cultural patrimony.